Piperacillin plus vancomycin in the therapy of febrile episodes in cancer patients. - Jadeja, L (1984)
Piperacillin and vancomycin were used as initial empirical therapy for 211 febrile episodes in cancer patients. The response rate in 95 episodes of documented infection was 72%. The response of bacteremias, soft tissue infections, and pneumonias was 78, 71, and 38%, respectively. The response in infections caused by gram-negative organisms was 73%. Only 6 of 10 Pseudomonas aeruginosa infections responded to therapy, although the organisms were sensitive in vitro to piperacillin. Of 14 infections caused by gram-positive organisms, 12 responded to this combination. No major side effects were observed with this regimen. Although the overall response rate with this antibiotic combination was comparable with other regimens used for neutropenic patients, superior results might be obtained by combining piperacillin with an extended-spectrum cephalosporin or an aminoglycoside.